Faktor Yang Mempengaruhi Rendahnya Minat WUS Dalam Menggunakan Kontrasepsi Medis Operatif Wanita (MOW) Di Desa Kota Tengah Kecamatan Dolok Masihul - ADE AYU PRAWITA (STIKES ADVAITA MEDIKA TABANAN, 2020)
Background: Family Planning is one of the most basic and primary preventive health services for women. The Female Operative Method (MOW) is an act of closing both the right and left egg cells so that there is no pregnancy. This MOW method greatly influences EFA interest, one of which is knowledge, parity, and husband support. Objective: The purpose of this study was to determine the effect of knowledge, parity, husband support on the low interest of EFA in using MOW. Methods: This type of research was an analytic survey with a cross-sectional design. This research was conducted in Kota Tengah Village, Dolok Masihul District, in March - October 2019. The population in this study was 64 respondents with purposive sampling technique. Data collection with primary, secondary and tertiary data. Data analysis used univariate and bivariate analysis. Results: Bivariate analysis study were obtained from the chi-square test data with a probability value of α = .05 from the knowledge variable to interest .015 <.05, parity to interest .071 <value α = .05, support of the husband to interest .068 <value α = .05. Conclusion: This study is that influence of knowledge, parity and husband support on the low interest of EFA in using MOW in Kota Tengah Village, Dolok Masihul sub-district in 2019 was found.